TRYOUT PSIKOTEST DENGAN ALGORITMA MERGE SORT UNTUK PENINGKATAN SCORING BERBASIS ANDROID - Fitri Latifah; Syarif Hidayatulloh (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2014)
Today.. the psychology test has become a very difficult problem, especially for the first time which done it, although there are many books with a variety of questions have been provided to try the ability to follow the psychology test but it cannot be guaranteed. Difficulties in spelling matter to get a high score is to make participants are desperate to keep practicing work on the problems and get a high score, so a lot of those who fail to follow. This can be overcome by recognizing the diverse forms matter. Now has a lot of methods to learn or practice of psychological tests. This phenomenon was the inspiration for the writer to help those who want to follow psychological tests to the buld application that are used to try out in psychology test. The application built using the merge sort algorithm than use to find the correct answers stored in the database answers with the answers given by the user. With the advancement of technology today, especially in the development of devices and limed gagget busy time time for everyone to learn to allow these aplications are used to practice psychology test with the aim to oncrease score psychological test